Management of the mitral valve in thoracoscopic trans-mitral myectomy for hypertrophic obstructive cardiomyopathyCentral MessagePerspective - Tong Tan, MD; Jian Liu, MD; Bingqi Fu, MD; Peijian Wei, MD; Wei Zhu, MD; Jian Zhuang, MD, PhD; Jimei Chen, MD, PhD; Huiming Guo, MD (JTCVS Techniques)
Objective: This study aimed to compare clinical outcomes of different mitral valve (MV) management methods in thoracoscopic transmitral myectomy (TTM) and guide surgeons' decision making for hypertrophic obstructive cardiomyopathy (HOCM). Methods: Seventy-three consecutive patients (41 females; mean age, 53.7 ± 13.6 years) with HOCM who underwent TTM between January 2019 and October 2022 were enrolled and divided into 3 groups according to MV surgical strategy. Clinical outcomes were analyzed and compared among the groups. Results: None of the patients experienced postoperative residual left ventricular outflow tract obstruction. Percentages of patients with mitral regurgitation (MR) grade ≥3+ (57.5% vs 1.4%) and systolic anterior motion (95.9% vs 2.7%) were significantly decreased postoperatively (P < .001 for both). The preoperative anterior mitral leaflet length was longer in patients in the anterior mitral leaflet direct reattachment group (median, 2.9 cm [interquartile range (IQR), 2.7-3.3 cm] vs 2.7 [IQR, 2.4-2.9 cm]; P = .018), but the postoperative coaptation length was shorter (mean, 8.3 ± 2.1 mm vs 11.1 ± 3.8 mm; P = .038). After a median echocardiography follow-up of 11.8 months, the left ventricular outflow tract gradient (LVOTG) and mitral regurgitation grades remained significantly improved in all 3 groups (P < .05 for all). Conclusions: Total TTM in selected patients is safe and effective, and all 3 MV management strategies can significantly reduce the LVOTG while improving MR. Mitral valvuloplasty is the preferred initial management strategy over valve replacement except in the scenario of irreparable intrinsic MV disease and valvuloplasty failure.